Teori 'Pinjam dan Pengaruh' Oleh Samuel M. Zwemer (1867-1952) dan Sanggahan Terhadapnya Menerusi Konsep Wihdah Al-Din Islam - Wan Mohd Fazrul Azdi Wan Razali (Universiti Sains Islam Malaysia, 2024)
Among the popular arguments used by the orientalists to discredit Islamic religion is the utilization of the Theory of Borrow and Influence. For instance, Samuel M. Zwemer had perfected his writings in demonstrating this theory through his noted work, Arabia the Cradle of Islam. In this ideal, Islam had gone through such examination and been rooted to the religions of Pagan Arab, Zoroastrianism, Judaism, Christianity and others for the resembling elements shared. This paper will refute this claim under the light of the concept of wihdah al-din, as stressed in the Islamic religion.